1986
DOI: 10.1159/000194906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Divided Doses of a Bronchodilator Aerosol and the Intervening Time Interval on the Forced Expiration

Abstract: Twelve patients with bronchial asthma participated in a blind, randomized, crossover study comparing the effects of 500 μg terbutaline in one inhalation, 125 μg in four inhalations taken in rapid succession, and 125 μg in four inhalations taken with an intervening time interval of 30 min. There were no significant differences between the three modes of inhalation of 500 μg terbutaline in any of the spirometric variables, i.e., 1-second forced expiratory volume, forced vital capacity, and maximal airflows when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Third, our study did not assess whether the effect of salbutamol inhaled at one time point is equivalent to that inhaled cumulatively over 90 min. However, previous studies have shown the dose effect of short‐acting bronchodilators to be independent of the time course of inhalation and we expect the effect of the higher doses of salbutamol (eg, 800 and 1200 μg) inhaled cumulatively to be very similar to that of 1200 μg inhaled in quick succession.…”
Section: Discussionmentioning
confidence: 88%
“…Third, our study did not assess whether the effect of salbutamol inhaled at one time point is equivalent to that inhaled cumulatively over 90 min. However, previous studies have shown the dose effect of short‐acting bronchodilators to be independent of the time course of inhalation and we expect the effect of the higher doses of salbutamol (eg, 800 and 1200 μg) inhaled cumulatively to be very similar to that of 1200 μg inhaled in quick succession.…”
Section: Discussionmentioning
confidence: 88%